Olivine-type composite positive electrode material and its manufacturing method and application, lithium-ion battery
Patent Information
- Application Number
- JP2024552093
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2022-06-30
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2042-06-30
AI Technical Summary
【0010】 上述の技術案によれば、本発明に係るオリビン型複合正極材料及びその製造方法と応用、リチウムイオン電池は、以下の有益な効果を奏する。
Smart Images

Figure 2025507881000001_ABST
Abstract
Description
[Technical field]
[0001] The present disclosure relates to the technical fields of new energy and lithium ion batteries, and in particular to an olivine-type composite positive electrode material and its manufacturing method and application, and a lithium ion battery. [Background technology]
[0002] The rapid development of the new energy vehicle power battery and storage battery market has prompted people to place higher requirements on the fast charging performance and safety performance of lithium-ion batteries. The positive electrode material of lithium-ion batteries is one of the important materials with the highest cost-to-quality ratio in lithium-ion batteries, and its performance greatly determines the energy density, fast charging performance, and safety performance of lithium-ion batteries. Among them, the olivine structure positive electrode material represented by lithium iron phosphate has become one of the mainstream positive electrode material systems in the current power and energy storage battery market due to its high energy density, excellent cycling performance and safety performance, low cost and price.
[0003] However, due to the special chemical composition and structure of the lithium iron phosphate LiFePO4 positive electrode material, the maximum discharge specific capacity can only reach 170mAh / g, the discharge voltage platform is usually below 3.4V, and the electronic conductivity is low, resulting in poor low temperature performance and multiplication performance. x Fe 1-x The PO4 cathode material can further improve the discharge voltage platform by replacing Fe with Mn based on LiFePO4, thereby increasing the energy density of the battery. x Fe 1-x PO4 has poorer electronic conductivity and serious Mn elution, which adversely affects the low-temperature performance, power supply performance, cycle performance, and safety performance of the battery, and therefore has not yet been put into practical industrial use. Summary of the Invention [Problem to be solved by the invention]
[0004] The objective of the present invention is to provide an olivine-type composite positive electrode material and its manufacturing method and application in lithium ion batteries, in order to overcome the above-mentioned problems in the existing technology. For lithium ion batteries, the olivine-type composite positive electrode material is a composite phase T m G n The composite phase is introduced into the positive electrode material in situ, so that the composite phase is uniformly composited with the crystal boundaries and surface of the substrate of the positive electrode material and is closely fused to the substrate of the positive electrode material, thereby improving the electronic conductivity and the stability of the surface structure during the use of the positive electrode material. m G n has a metal-like electronic structure and generally exhibits properties such as low electrical resistivity (<10 Ω·cm), strong chemical adsorption ability, and chemical stability. Therefore, the composite positive electrode material containing the composite phase has high electrical conductivity and excellent chemical stability, and is suitable for the fields of supercapacitors, lithium ion batteries, lithium sulfur batteries, etc. In particular, the lithium ion battery containing the composite positive electrode material has significantly improved fold performance and cycle life. [Means for solving the problem]
[0005] In order to achieve the above object, in a first aspect of the present invention, there is provided an olivine-type composite positive electrode material, comprising: The composite positive electrode material includes a substrate and a composite phase; The substrate has a composition according to formula I: Li x M 1 y Mn z Fe 1-z-u M 2 u (PO4) w (RO a ) b Cv (Formula I) Among them, 0.5≦x<1.3, 0≦y≦0.5, 0 <z≦1、0≦u≦0.01、0<w≦1、0<v≦0.05、0≦a≦8、0≦b≦1、M 1 is at least one element selected from Mg, Na, and K, and M 2is at least one element selected from Ga, Sn, V, Y, Mo, Al, Mg, Ce, Ti, Zr, Nb, Si, W, and In, and R is at least one element selected from Si, Cl, Br, S, Sb, and Sn, The composite phase has a composition according to formula II: T m G n (Formula II) There is provided an olivine-type composite positive electrode material in which 0.1≦m≦5, 0.1≦n≦5, T is at least one element selected from Ti, Mo, Co, W, Zn, Cu, B, V, Nb, Ta, Pd, Cr, Ag, Al, Mn, Sn, Mg, Sc, Zr, and Hf, and G is an element selected from N and / or C.
[0006] In a second aspect of the present invention, there is provided a method for producing an olivine-type composite cathode material, comprising the steps of: (1) performing a first mixing process on a compound containing a T element and a compound containing a G element to obtain a first mixture, and performing a first heat treatment on the first mixture in the presence of a protective atmosphere to obtain a compound containing T and G; Lithium source, carbon source, phosphorus source, optional iron source, manganese source, optional R source, optional M 1 (2) subjecting the source and, optionally, the M2 source and the solvent to a second mixture to obtain a second mixture, and grinding the second mixture to obtain a slurry; (3) performing a third mixing and drying of the compound containing T and G and the slurry to obtain a powder; and (4) subjecting the powder to a second heat treatment in the presence of a non-oxidizing gas atmosphere to crush it to obtain the olivine-type composite cathode material.
[0007] In a third aspect of the present invention, there is provided an olivine-type composite cathode material produced by the above-described method.
[0008] In a fourth aspect of the present invention, there is provided an application of the above-mentioned olivine-type composite cathode material in at least one of a supercapacitor, a lithium-ion battery, and a lithium-sulfur battery.
[0009] In a fifth aspect of the present invention, there is provided a lithium-ion battery comprising the olivine-type composite cathode material described above. Effect of the Invention
[0010] According to the above technical solutions, the olivine-type composite positive electrode material and its manufacturing method and application in the lithium ion battery according to the present invention can achieve the following beneficial effects:
[0011] (1) In the olivine-type composite positive electrode material according to the present invention, the substrate and the composite phase T m G n The composite phase is introduced into the positive electrode material in situ, so that the composite phase is uniformly composited with the crystal boundary and surface of the substrate of the positive electrode material and closely fused to the substrate of the positive electrode material. This improves the electronic conductivity and stability of the surface structure during the use of the positive electrode material, and makes the composite phase exhibit properties such as low electrical resistivity (<10 Ω·cm), strong chemical adsorption ability, and chemical stability. This makes it suitable for fields such as supercapacitors, lithium ion batteries, and lithium sulfur batteries, and in particular, the lithium ion batteries containing the composite positive electrode material have significantly improved power performance and cycle life.
[0012] (2) In the method for producing the olivine-type composite positive electrode material according to the present invention, a mixture of a compound containing T element and a compound containing G element is heat-treated in a protective atmosphere, and the compound containing T and G obtained by the heat treatment is introduced into the composite olivine-type positive electrode material. As a result, the composite phase formed by the compound containing T and G can be uniformly composited on the crystal boundary and surface of the substrate of the positive electrode material, and can be closely fused to the substrate of the positive electrode material. As a result, the electronic conductivity and stability of the surface structure during the use of the positive electrode material are improved, and the supply source of raw materials is abundant, the production cost is low, and the whole process is easy to industrialize.
[0013] (3) In the manufacturing method of the olivine-type composite positive electrode material of the present invention, the synthesis of the material substrate, carbon coating, and the composite material containing T and G with the substrate can be completed by only one sintering process, which shortens the manufacturing time of the sample, effectively saves energy, and reduces carbon emissions. [Brief description of the drawings]
[0014] [Figure 1] FIG. 1 is a distribution diagram of T of the sintered product of Example 3. [Diagram 2] FIG. 11 is a distribution diagram of T of the sintered product of Comparative Example 3. [Diagram 3] FIG. 13 is a diagram showing charge / discharge curves at 0.1C magnification and 2C magnification of liquid ion batteries assembled using the positive electrode materials of Comparative Example 3 and Example 3. [Figure 4] FIG. 1 shows the cycling performance at 1C of liquid ion batteries assembled with the positive electrode materials of Comparative Example 3 and Example 3. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] The endpoints of the ranges and any values disclosed herein are not intended to be limiting to the exact ranges or values, but rather should be understood to include the values that are close to them. In the case of numerical ranges, the endpoints of each range, and the endpoints and the individual point values, can be combined to form one or more new numerical ranges. These numerical ranges are to be considered as specifically disclosed in this application.
[0016] In a first aspect of the present disclosure, there is provided an olivine-type composite cathode material, comprising: The composite positive electrode material includes a substrate and a composite phase; The substrate has a composition according to formula I: Li x M 1 y Mn z Fe 1-z-u M 2 u (PO4) w (RO a )b Cv (Formula I) Among them, 0.5≦x<1.3, 0≦y≦0.5, 0 <z≦1、0≦u≦0.01、0<w≦1、0<v≦0.05、0≦a≦8、0≦b≦1、M 1 is at least one element selected from Mg, Na, and K, and M 2 is at least one element selected from Ga, Sn, V, Y, Mo, Al, Mg, Ce, Ti, Zr, Nb, Si, W, and In, and R is at least one element selected from Si, Cl, Br, S, Sb, and Sn, The composite phase has a composition according to formula II: T m G n (Formula II) There is provided an olivine-type composite positive electrode material in which 0.1≦m≦5, 0.1≦n≦5, T is at least one element selected from Ti, Mo, Co, W, Zn, Cu, B, V, Nb, Ta, Pd, Cr, Ag, Al, Mn, Sn, Mg, Sc, Zr, and Hf, and G is an element selected from N and / or C.
[0017] In the present invention, the olivine type composite positive electrode material is a composite phase T m G n The composite phase is introduced into the positive electrode material in situ, so that the composite phase is uniformly composited with the crystal boundaries and surface of the substrate of the positive electrode material and is closely integrated with the substrate of the positive electrode material, thereby improving the electronic conductivity and the stability of the surface structure during the use of the positive electrode material.
[0018] Furthermore, the composite phase T m G n (e.g. TiN, MoN, Co3N, W2N, VN, etc.) have electronic structures similar to metals and usually exhibit properties such as low electrical resistivity (<10 Ω·cm), strong chemical adsorption ability, chemical stability, etc. Therefore, the composite positive electrode material containing the composite phase has high electrical conductivity and excellent chemical stability, and is suitable for fields such as supercapacitors, lithium ion batteries, and lithium sulfur batteries. In particular, the lithium ion battery containing the composite positive electrode material has significantly improved fold performance and cycle life.
[0019] Further, in formula I, 0.9≦x<1.1, 0 <y≦0.01、0.5≦z≦1、0<u≦0.005、0.5≦w<1、0.001<v≦0.03、0≦a≦4、0<b≦0.1。
[0020] Furthermore, in formula II, 0.5≦m≦3, 1≦n≦5, T is at least one element selected from Ti, Mo, Co, W, Zn, Cu, B, V, Nb, Ta, Cr, Ag, Al, Mn, Sn, Mg, Sc, and Zr.
[0021] According to the present invention, based on the total weight of the composite positive electrode material, the content of the composite phase is 0.01-10 wt %.
[0022] In the present invention, the content of the composite phase in the composite positive electrode material is measured using ICP method.
[0023] In the present invention, when the content of the composite phase in the composite positive electrode material satisfies the above-mentioned range, the electronic conductivity and structural stability of the substrate interface can be improved, so that the composite positive electrode material has low powder electrical resistivity and excellent surface stability, and when the composite positive electrode material is used in a lithium ion battery, the charging performance and cycling performance of the lithium ion battery are significantly improved, and the amount of manganese elution is also reduced.
[0024] Furthermore, the content of the composite phase is 0.01 to 1 wt % based on the total weight of the composite positive electrode material.
[0025] According to the present invention, the pressed density of the composite positive electrode material is 1.5 to 3 g / cm 3 It is.
[0026] In the present invention, the composite positive electrode material has a high compression density, and when the composite positive electrode material is used in a lithium ion battery, more positive electrode material can be loaded in the same volume, thereby improving the capacity and energy density of the battery.
[0027] Furthermore, the compressed density of the composite positive electrode material is 2 to 3 g / cm3 It is.
[0028] According to the present invention, the electrical resistivity of the composite positive electrode material is ≦2500 Ω / cm.
[0029] In the present invention, the composite positive electrode material has low electrical resistivity, which indicates that the composite positive electrode material has high electrical conductivity, so that when the composite positive electrode material is used in a lithium ion battery, it can improve the charge-discharging performance and cycle life of the lithium ion battery.
[0030] Furthermore, the electrical resistivity of the composite positive electrode material is ≦1000 Ω / cm.
[0031] According to the present invention, in the composite positive electrode material, 0.5≦m / n≦7.
[0032] In the present invention, when the m / n ratio of the composite positive electrode material satisfies the above-mentioned range, the composite phase of the composite positive electrode material is a pure phase, which allows the advantages of the composite phase, such as high electronic conductivity and structural stability, to be fully exerted, and as a result, the lithium ion battery including the composite positive electrode material has excellent charge capacity and cycle performance.
[0033] In the present invention, the content m of the T element in the composite positive electrode material is measured by EDS areal scan, and the content n of the G element is also measured by EDS areal scan.
[0034] Furthermore, in the composite positive electrode material, 1≦m / n≦5.
[0035] According to the present invention, the average particle size D of the composite positive electrode material 50 The thickness is 0.5 to 20 μm, and preferably 1 to 15 μm.
[0036] According to the invention, the composite cathode material has an EDS elemental analysis with a standard variance of m / n at any position of ≦1%.
[0037] In the present invention, when EDS elemental analysis of the composite positive electrode material is performed, the composite phase T m G n When the standard dispersion of the molar ratio m / n of T and G elements in the composite phase T m G n are uniformly compounded in the positive electrode material, and all of them exist in the form of T m G n It indicates that the composite positive electrode material is a pure phase. This ensures the low resistivity and structural stability of the composite phase, and as a result, the electrical resistivity of the entire composite positive electrode material is maintained at a low level. During charging and discharging, the smooth flow of the electron transmission channel is ensured, and at the same time, the stability of the surface structure is ensured, and the metal elution rate is reduced. When this composite positive electrode material is used in a lithium ion battery, the power supply performance and cycle performance of the lithium ion battery are significantly improved.
[0038] Furthermore, the standard dispersion of m / n is ≦0.8%.
[0039] In a second aspect of the present invention, there is provided a method for producing an olivine-type composite cathode material, comprising the steps of: (1) performing a first mixing process on a compound containing a T element and a compound containing a G element to obtain a first mixture, and performing a first heat treatment on the first mixture in the presence of a protective atmosphere to obtain a compound containing T and G; Lithium source, carbon source, phosphorus source, optional iron source, manganese source, optional R source, optional M 1 (2) subjecting the source and, optionally, the M2 source and the solvent to a second mixture to obtain a second mixture, and grinding the second mixture to obtain a slurry; (3) performing a third mixing and drying of the compound containing T and G and the slurry to obtain a powder; and (4) subjecting the powder to a second heat treatment in the presence of a non-oxidizing gas atmosphere to crush it to obtain the olivine-type composite cathode material.
[0040] In the present invention, a mixture of a compound containing T element and a compound containing G element is heat-treated in a protective atmosphere, and the compound containing T and G obtained by the heat treatment is introduced into a composite olivine type positive electrode material. In this way, the composite phase formed by the compound containing T and G can be uniformly composited on the crystal boundary and surface of the substrate of the positive electrode material, and can be closely fused to the substrate of the positive electrode material. This improves the electronic conductivity and stability of the surface structure during the use of the positive electrode material, and the supply source of raw materials is abundant, the manufacturing cost is low, and the whole process is easy to industrialize.
[0041] Furthermore, in the manufacturing method of the present invention, the synthesis of the material substrate, carbon coating, and compounding of the T and G-containing compounds with the substrate material can be completed in a single sintering process, which shortens the manufacturing time of the sample, effectively saves energy, and reduces carbon emissions.
[0042] According to the present invention, in step (1), the compound containing the element T is at least one selected from the group consisting of an elemental T, an oxide of T, a nitrate of T, and a hydroxide of T.
[0043] In the present invention, there is no particular limitation on the shape of the oxide of T. For example, the oxide of T may be at least one selected from the group consisting of nanoparticles, nanosheets, and nanowires.
[0044] In the present invention, the average particle diameter D of the oxide of T 50 is 0.001 to 1 μm.
[0045] According to the present invention, the compound containing the G element is at least one selected from nitrogen gas, ammonia gas, melamine, polydopamine, urea, glucose, starch, sucrose, and graphite.
[0046] Furthermore, the compound containing the G element is at least one selected from the group consisting of nitrogen gas, ammonia gas, urea, and glucose.
[0047] According to the present invention, the conditions of the first heat treatment include a heat treatment temperature of 400 to 1000° C. and a heat treatment time of 2 to 8 hours.
[0048] In the present invention, by subjecting the first mixture to a heat treatment under the above-mentioned conditions, the compound containing T element and the compound containing G element can be completely converted into a pure-phase compound (nitride and / or carbide) containing T and G. This ensures that the composite phase in the composite positive electrode material obtained by combining the compound containing T and G with the slurry is a pure phase, and the resulting composite positive electrode material has high electronic conductivity and good structural stability. When the composite positive electrode material is used in a lithium ion battery, the power supply performance and cycle performance of the lithium ion battery can be significantly improved.
[0049] Further, the conditions of the first heat treatment include a heat treatment temperature of 500 to 800° C. and a heat treatment time of 4 to 10 hours.
[0050] According to the present invention, the molar ratio of the moles of T in the compound containing a T element to the moles of G in the compound containing a G element is 0.5 to 7:1.
[0051] In the present invention, when the molar ratio of the compound containing element and the compound containing G element is within the above-mentioned range, the compound containing T and G is compounded with the slurry to produce the composite positive electrode material, and the composite phase in the composite positive electrode material obtained can be ensured to be a pure phase, and the composite positive electrode material thus produced has high electronic conductivity and good structural stability. When the composite positive electrode material is used in a lithium ion battery, the multiplication performance and cycle performance of the lithium ion battery can be significantly improved.
[0052] In the present invention, the conditions of the first mixing are not particularly limited, but it is sufficient that the compound containing element T and the compound containing element G can be mixed sufficiently uniformly. Preferably, the conditions of the first mixing include a mixing rotation speed of 100 to 1000 rpm and a mixing time of 1 to 10 hours.
[0053] In the present invention, the method of the first mixing is not particularly limited, and the first mixing can be realized by the method in the art. Specifically, the method of the first mixing is at least one selected from a mechanical planetary mixer, a mechanical high-speed mixer, a ball grinder, and a sand grinder.
[0054] In the present invention, there is no particular limitation on the type of protective atmosphere, and protective atmospheres commonly used in this field, such as nitrogen and / or argon, can be selected.
[0055] According to the present invention, in step (2), the lithium source is at least one selected from lithium carbonate, lithium hydroxide, lithium oxide, and lithium nitrate.
[0056] According to the present invention, the phosphorus source is at least one selected from phosphoric acid, metaphosphoric acid, pyrophosphoric acid, ammonium dihydrogen phosphate, diamine hydrogen phosphate, and phosphorus oxide.
[0057] According to the present invention, the carbon source is at least one selected from glucose, sucrose, starch, graphene, and carbon nanotubes.
[0058] According to the present invention, the iron source is at least one selected from iron phosphate, iron oxalate, iron acetate, iron oxide, and iron oxyhydroxide.
[0059] According to the present invention, the manganese source is at least one selected from manganese oxide, manganese carbonate, and manganese nitrate.
[0060] According to the present invention, the R source is selected from a compound containing at least one element selected from the group consisting of Si, Cl, Br, S, Sb, and Sn. Specifically, the R source is at least one selected from the group consisting of an acid containing an R element, an oxide containing an R element, and a hydroxide containing an R element.
[0061] According to the present invention, the M 1The source is selected from compounds containing at least one element selected from Mg, Na and K. 1 Source: M 1 Oxides containing elements, M 1 Hydroxides containing elements and M 1 At least one kind selected from carbonates containing elements.
[0062] According to the present invention, the M 2 The source is selected from compounds containing at least one element selected from the group consisting of Ga, Sn, V, Y, Mo, Al, Mg, Ce, Ti, Zr, Nb, Si, W and In. 2 Source: M 2 Oxides containing elements, M 2 Hydroxides containing elements and M 2 At least one kind selected from carbonates containing elements.
[0063] According to the present invention, the solvent is at least one selected from water, ethanol, methanol, NMP and isopropanol.
[0064] According to the present invention, the moles of the lithium source as Li, the moles of the phosphorus source as P, the moles of the carbon source as C, the moles of the iron source as Fe, the moles of the manganese source as Mn, the moles of the R source as R, the moles of the M 1 Source M 1 and the molar ratio M 2 Source M 2 The molar ratio of the phosphorus source, the manganese source, and the carbon source is (0.5-1.3):(0-1):(0-0.05):(0-1):(0-1):(0-1):(0-0.5):(0-0.01), and the dosages of the phosphorus source, the manganese source, and the carbon source are not 0.
[0065] In the present invention, a lithium source, a phosphorus source, a carbon source, an iron source, a manganese source, an R source, an M 1 Source, M. 2When the source satisfies the above range, the resulting composite positive electrode material has high ionic conductivity and excellent structural stability, and when used in a lithium ion battery, the charge / discharge capacity, charge / discharge performance and cycle performance of the lithium ion battery are significantly improved.
[0066] Further, the moles of the lithium source as Li, the moles of the phosphorus source as P, the moles of the carbon source as C, the moles of the iron source as Fe, the moles of the manganese source as Mn, the moles of the R source as R, the moles of the M 1 Source M 1 and the molar ratio M 2 Source M 2 The molar ratio of the M is (0.9-1.1):(0.5-1):(0.001-0.03):(0-0.495):(0.5-1):(0-0.1):(0-0.01):(0-0.005), 1 source, the iron source, the R source, and the M 2 The content of any source is not 0.
[0067] According to the present invention, the solid content of the slurry is 10-60 wt%.
[0068] Furthermore, the solid content of the slurry is 2 to 50 wt %.
[0069] In the present invention, there is no particular requirement for the amount of the solvent, so long as the solid content of the slurry satisfies the above range.
[0070] According to the present invention, the average particle size D of the slurry 50 is 0.1 to 1 μm.
[0071] In the present invention, the average particle size D of the slurry 50 When the average particle size of the slurry satisfies the above-mentioned range, it is advantageous to increase the tap density of the powder after drying together with the compound containing T and G, and to improve the packing amount and sintering ability. Furthermore, controlling the average particle size of the slurry so as to satisfy the above-mentioned range is particularly suitable for spray drying.
[0072] Furthermore, the average particle size D of the slurry 50 is 0.1 to 0.8 μm.
[0073] In the present invention, the conditions of the second mixing are not particularly limited, but the lithium source, phosphorus source, carbon source, iron source, manganese source, R source, M 1 Source, M. 2 It is only necessary that the source be able to be mixed sufficiently uniformly with the solvent.
[0074] In the present invention, there is no particular limitation on the polishing conditions, but the average particle size D of the slurry 50 It is only necessary that the above-mentioned range is satisfied. Preferably, the polishing conditions include a polishing rotation speed of 500 to 2000 rpm and a polishing time of 1 to 10 hours.
[0075] In the present invention, there is no particular limitation on the polishing method, and the polishing can be achieved by adopting methods in this field. Specifically, the polishing method is at least one selected from stirrer polishing, ball polishing, and sand polishing.
[0076] In the present invention, the polishing includes polishing the second mixture to obtain a slurry, and the polishing equipment includes one or more of a stirrer mill, a ball mill, and a sand mill.
[0077] According to the present invention, in step (3), the solid-liquid ratio of the compound containing T and G to the slurry is 0.000001 to 10 g / mL.
[0078] In the present invention, when the solid-liquid ratio of the compound containing T and G and the slurry satisfies the above-mentioned range, the compound containing T and G has good dispersibility in the slurry, and in the positive electrode material produced by this, the composite phase and the substrate are uniformly composited without aggregation, and the lithium ion battery containing the composite positive electrode material has more stable electrochemical performance.
[0079] Furthermore, the solid-liquid ratio of the compound containing T and G and the slurry is 0.00001 to 1 g / mL.
[0080] In the present invention, there is no particular limitation on the third mixing conditions, so long as the compound containing T and G and the slurry can be mixed sufficiently uniformly.
[0081] In the present invention, there is no particular limitation on the drying conditions or drying equipment, as long as the mixture of the compound containing T and G and the slurry can be sufficiently dried. The drying equipment may be at least one selected from a spray dryer, a forced air drying oven, a vacuum drying oven, a freeze dryer, a flash dryer, and the like.
[0082] According to the present invention, in step (4), the conditions of the second heat treatment include a heat treatment temperature of 400 to 1000° C. and a heat treatment time of 4 to 12 hours.
[0083] In the present invention, by subjecting the powder to the second heat treatment under the above conditions, T m G n was compounded in situ, and the compound phase T m G n is tightly bonded to the substrate. At the same time, a carbon coating layer can be uniformly formed on the surface of the composite phase and the substrate. The composite positive electrode material thus prepared has high electrical conductivity and excellent cycling performance. When the positive electrode material is used in a lithium ion battery, the charging performance and cycling performance of the lithium ion battery are significantly improved.
[0084] Further, the conditions of the second heat treatment include a heat treatment temperature of 500 to 900° C. and a heat treatment time of 6 to 10 hours.
[0085] In the present invention, there is no particular limitation on the type of non-oxidizing gas atmosphere, and any non-oxidizing gas atmosphere commonly used in this field, such as nitrogen or argon, may be used.
[0086] In the present invention, there is no particular limitation on the crushing equipment, and at least one of equipment commonly used in this field, such as a mechanical mill, a colloid mill, and an air jet mill, may be used.
[0087] In a third aspect of the present invention, there is provided an olivine-type composite cathode material produced by the above-described method.
[0088] In a fourth aspect of the present invention, there is provided an application of the above-mentioned olivine-type composite cathode material in at least one of a supercapacitor, a lithium-ion battery, and a lithium-sulfur battery.
[0089] In a fifth aspect of the present invention, there is provided a lithium-ion battery comprising the olivine-type composite cathode material described above.
[0090] In the present invention, when the olivine-type composite positive electrode material is a positive electrode material containing Mn, that is, when z is not 0, when the olivine-type composite positive electrode material is used in a lithium ion battery, the lithium ion battery becomes a liquid lithium ion battery. After 1000 cycles at 45°C, the amount of manganese eluted from the negative electrode of the liquid lithium ion battery is ≦≦3000 ppm, preferably 500 to 2000 ppm.
[0091] The present invention will now be described in detail with reference to the following examples. The composition of the composite positive electrode material is measured by ICP method. The content of the composite phase in the composite cathode material is also measured by ICP method. The pressed density of the composite positive electrode material is measured by a powder pressing densitometer method. The electrical resistivity of the composite positive electrode material is measured by electrical resistivity meter method. The content of G element in the composite positive electrode material is measured by EDS surface scan, and the content and distribution of T element are also measured by EDS surface scan. The raw materials used in the examples and comparative examples are commercially available products.
[0092] Example 1
[0093] (1) 10 g of TiO2 nanoparticles with an average particle size of 0.05 μm and 80 g of urea are mixed in a ball grinding can at 600 rpm for 5 h, and the mixture is heat-treated in a tube furnace at 550 °C under a nitrogen gas atmosphere for 10 h to obtain TiN nanoparticles. Here, the molar ratio of T of the compound containing T element to G of the compound containing G element is 1:1.
[0094] (2) 24.04 g of lithium carbonate (lithium source), 19.89 g of iron oxide (iron source), 44.12 g of manganese carbonate (manganese source), 73.24 g of ammonium dihydrogen phosphate (phosphorus source), and 14.34 g of glucose (carbon source) were mixed in 200 g of pure water, and the mixture was ball-milled in a planetary ball mill at a rotation speed of 500 rpm for 6 h to obtain D 50 Here, moles of Li of the lithium source, moles of P of the phosphorus source, moles of C of the carbon source, moles of Fe of the iron source, moles of Mn of the manganese source, and M 2 Source M 2 The molar ratio of the molar amounts of the components as: 1:1:0.1:0.4:0.599:0.001. The solids content of the slurry is 45 wt%.
[0095] (3) 0.3 g of TiN nanoparticles are mechanically stirred into the slurry obtained in step (2) for 30 min to obtain a uniformly dispersed mixed slurry, and the mixed slurry is dried in a spray dryer to obtain a powder, where the solid-liquid ratio of the TiN nanoparticles to the slurry is 0.0001 g / mL.
[0096] (4) The powder obtained in step (3) is treated in a tube furnace under a nitrogen gas atmosphere at 750 °C for 8 hours to obtain a sintered product, which is then pulverized in an air jet mill to obtain the olivine-type composite positive electrode material A1. The dosage and process conditions of each material during the manufacturing process are shown in Table 1.
[0097] Some of the sintered products were cut by plasma beam to obtain the material cross section, and the material cross section was surface scanned by EDS to test the distribution uniformity of Ti element, the results of which are shown in Table 2.
[0098] The composition, content of composite phase, particle size, pressed density, electrical resistivity and T / G of the olivine-type composite cathode material A1 were tested, and the results are shown in Table 2.
[0099] Example 2
[0100] (1) 10 g of Co3O4 nanosheets with an average particle size of 0.09 μm and 80 g of melamine are mixed in a ball grinding can at 600 rpm for 5 h, and the mixture is heat-treated in a tube furnace at 600 °C under a nitrogen gas atmosphere for 10 h to obtain Co3N nanoparticles. Here, the molar ratio of T of the compound containing T element to G of the compound containing G element is 3:1.
[0101] (2) 24.04 g of lithium carbonate (lithium source), 95.93 g of iron phosphate (iron source, phosphorus source), 44.16 g of manganese carbonate (manganese source), 0.04 g of titanium dioxide (M 2 14.34 g of glucose (carbon source) was mixed with 200 g of pure water, and the mixture was ball-milled in a planetary ball mill at 500 rpm for 6 h. 50 Here, moles of lithium source Li, moles of phosphorus source P, moles of carbon source C, moles of iron source Fe, moles of manganese source Mn, moles of M 2 Source M 2 The molar ratio of the components as 1:1:0.1:0.4:0.599:0.001 and the solids content of the slurry was 45 wt%.
[0102] (3) 0.2 g of Co3N nanoparticles are mechanically stirred into the slurry obtained in step (2) for 30 min to obtain a uniformly dispersed mixed slurry, and the mixed slurry is dried in a spray dryer to obtain a powder, where the solid-liquid ratio of the Co3N nanoparticles to the slurry is 0.001 g / mL.
[0103] (4) The powder obtained in step (3) is treated in a tube furnace under a nitrogen gas atmosphere at 800°C for 8 hours to obtain a sintered product, which is then pulverized in an air jet mill to obtain an olivine-type composite positive electrode material A2.
[0104] A part of the sintered material was cut by plasma beam to obtain the material cross section, and the material cross section was surface scanned by EDS to test the distribution uniformity of Co element, the results of which are shown in Table 1.
[0105] The composition, content of composite phase, particle size, pressed density, electrical resistivity and T / G of the olivine-type composite cathode material A2 were tested, and the results are shown in Table 1.
[0106] Example 3
[0107] (1) 10 g of MoO3 nanowires with an average particle size of 0.07 μm are heat-treated in a tube furnace under an ammonia gas atmosphere at 700 °C for 10 h to obtain MoN nanoparticles. Here, the molar ratio of T of the compound containing T element to G of the compound containing G element is 1:1.
[0108] (2) 24.28 g lithium carbonate (lithium source), 99.96 g iron nitrate (iron source), 132.83 g manganese nitrate (manganese source), 73.52 g phosphoric acid (phosphorus source), 0.17 g niobium oxide (M 2 62.52 g of glucose (carbon source) was mixed with 200 g of pure water, and the mixture was stirred for 6 hours at 300 rpm using a mechanical mixer to obtain a slurry. Here, the moles of the lithium source (Li), the moles of the phosphorus source (P), the moles of the carbon source (C), the moles of the iron source (Fe), the moles of the manganese source (Mn), and the moles of the manganese source (Mn) were calculated. 2 Source M 2 The molar ratio of the molar amounts of the components as are 1:1:0.1:0.398:0.6:0.002 and the solids content of the slurry is 45 wt%.
[0109] (3) 0.5 g of MoN nanoparticles are mechanically stirred into the slurry obtained in step (2) for 30 min to obtain a uniformly dispersed mixed slurry, and the mixed slurry is dried in a vacuum drying oven to obtain a dry gel powder, where the solid-liquid ratio of the MoN nanoparticles to the slurry is 0.0001 g / mL.
[0110] (4) The powder obtained in step (3) is treated in a tube furnace under a nitrogen gas atmosphere at 760° C. for 8 hours to obtain a sintered product, which is then pulverized in an air jet mill to obtain the olivine-type composite positive electrode material A3.
[0111] A part of the sintered material was cut by plasma beam to obtain the material cross section, and the surface was scanned by EDS to test the distribution uniformity of Mo element, and the results are shown in Table 1.
[0112] The composition, content of composite phase, particle size, pressed density, electrical resistivity and T / G of the olivine-type composite positive electrode material A3 were tested, and the results are shown in Table 1.
[0113] Example 4
[0114] (1) 10 g of V2O5 nanoparticles with an average particle size of 0.05 μm and 20 g of urea are mixed in a ball grinding can at 600 rpm for 5 h, and the mixture is heat-treated in a tube furnace at 550 °C for 10 h under an ammonia gas atmosphere to obtain VN nanoparticles. Here, the molar ratio of T of the compound containing T element to G of the compound containing G element is 1:1.
[0115] (2) 24.04 g lithium carbonate (lithium source), 95.58 g ammonium manganese ferric phosphate (phosphorus source, iron source, manganese source), 14.34 g glucose (carbon source), 0.06 g magnesium carbonate (M 1 source), niobium oxide 0.17g (M 2 The mixture was ball-milled in a planetary ball mill at a rotation speed of 500 rpm for 6 h, and then D 50Here, moles of Li of the lithium source, moles of P of the phosphorus source, moles of C of the carbon source, moles of Fe of the iron source, moles of Mn of the manganese source, and M 1 Source M 1 Molar as M 2 Source M 2 The molar ratio of the components as 1:1:0.1:0.398:0.6:0.001:0.002 and the solids content of the slurry was 45 wt%.
[0116] (3) 0.3 g of VN nanoparticles are mechanically stirred for 30 min into the slurry obtained in step (2) to obtain a mixed slurry in which the VN nanoparticles are uniformly dispersed, and the mixed slurry is dried in a spray dryer to obtain a powder. Here, the solid-liquid ratio of the VN nanoparticles to the slurry is 0.0001 g / mL.
[0117] (4) The powder obtained in step (3) is treated in a tube furnace under a nitrogen gas atmosphere at 750°C for 8 hours to obtain a sintered product, which is then pulverized in an air jet mill to obtain the olivine-type composite positive electrode material A4.
[0118] A part of the sintered material was cut by plasma beam to obtain the material cross section, and the surface was scanned by EDS to test the distribution uniformity of V element, and the results are shown in Table 1.
[0119] The composition, content of composite phase, particle size, pressed density, electrical resistivity and T / G of the olivine-type composite cathode material A4 were tested, and the results are shown in Table 1.
[0120] Example 5
[0121] (1) B2O3 nanosheets with an average particle size of 0.09 μm and glucose are mixed in a ball grinding can at 600 rpm for 5 h, and the mixture is heat-treated in a tube furnace at 1800 °C for 5 h under a nitrogen gas atmosphere to obtain B4C nanoparticles, where the molar ratio of T of the compound containing T element to G of the compound containing G element is 4:1.
[0122] (2) 24.04 g lithium carbonate (lithium source), 111.92 g iron phosphate (phosphorus source, iron source), 33.12 g manganese carbonate (manganese source), 0.04 g titanium dioxide (M 2 14.34 g of glucose (carbon source) was mixed with 200 g of pure water, and the mixture was ball-milled in a planetary ball mill at 500 rpm for 6 h. 50 Here, moles of lithium source Li, moles of phosphorus source P, moles of carbon source C, moles of iron source Fe, moles of manganese source Mn, moles of M 2 Source M 2 The molar ratio of the components as 1:1:0.1:0.3:0.699:0.001 and the solids content of the slurry was 45 wt%.
[0123] (3) 0.2 g of B4C nanoparticles are mechanically stirred for 30 min into the slurry obtained in step (2) to obtain a uniformly dispersed mixed slurry, which is then dried in a spray dryer to obtain a powder, where the solid-liquid ratio of the B4C nanoparticles to the slurry is 0.00015 g / mL.
[0124] (4) The powder obtained in step (3) is treated in a tube furnace under a nitrogen gas atmosphere at 800°C for 8 hours to obtain a sintered product, which is then pulverized in an air jet mill to obtain the olivine-type composite positive electrode material A5.
[0125] A part of the sintered material was cut by plasma beam to obtain the material cross section, and the surface was scanned by EDS to test the distribution uniformity of B element, and the results are shown in Table 1.
[0126] The composition, composite phase content, particle size, pressed density, electrical resistivity and T / G of the olivine-type composite cathode material A5 were tested, and the results are shown in Table 1.
[0127] Example 6
[0128] (1) 10 g of TiO2 nanoparticles with an average particle size of 0.05 μm and 80 g of urea are mixed in a ball grinder at 600 rpm for 5 h, and the mixture is heat-treated in a tube furnace at 550 °C for 10 h under a nitrogen gas atmosphere to obtain TiN nanoparticles. Here, the molar ratio of T of the compound containing T element to G of the compound containing G element is 1:1.
[0129] (2) 10 g of TiO2 nanoparticles with an average particle size of 0.05 μm and 100 g of glucose are mixed in a ball grinding can at 600 rpm for 5 h, and the mixture is heat-treated in a tube furnace at 550 °C for 10 h under a nitrogen gas atmosphere to obtain TiC nanoparticles. Here, the molar ratio of T of the compound containing T element to G of the compound containing G element is 1:1.
[0130] (3) 24.04 g of lithium carbonate (lithium source), 19.89 g of iron oxide (iron source), 44.12 g of manganese carbonate (manganese source), 72.5 g of ammonium dihydrogen phosphate (phosphorus source), 0.6 g of silicon dioxide (R source), and 14.34 g of glucose (carbon source) were mixed with 200 g of pure water, and the mixture was ball-milled in a planetary ball mill at a rotation speed of 500 rpm for 6 h, and D 50 A slurry having a particle size of 0.62 μm is obtained, in which the molar ratio of the lithium source (Li), the phosphorus source (P), the carbon source (C), the iron source (Fe), the manganese source (Mn), and the R source (R) is 1:1:0.1:0.4:0.6:0.01, and the solid content of the slurry is 45 wt %.
[0131] (4) 0.15 g of TiN nanoparticles and 0.15 g of TiC nanoparticles are mechanically stirred for 30 min into the slurry obtained in step (2) to obtain a uniformly dispersed mixed slurry, which is then dried with a spray dryer to obtain a powder, where the solid-liquid ratio of the TiN / TiC nanoparticles to the slurry is 0.0001 g / mL.
[0132] (5) In the same manner as in step (1) of Example 1, an olivine-type composite positive electrode material A6 is obtained.
[0133] A part of the sintered material was cut by plasma beam to obtain the material cross section, and the surface was scanned by EDS to test the distribution uniformity of Ti element, and the results are shown in Table 1.
[0134] The composition, composite phase content, particle size, pressed density, electrical resistivity and T / G of the olivine-type composite cathode material A6 were tested, and the results are shown in Table 1.
[0135] Comparative Example 1
[0136] The positive electrode material is produced according to the method of Example 1, except that:
[0137] Not carrying out step (1); and The other is not to add TiN nanoparticles in step (3).
[0138] After the olivine-type positive electrode material D1 was prepared, the composition, content of composite phases, particle size, pressed density and electrical resistivity of the olivine-type composite positive electrode material D1 were tested, and the results are shown in Table 1.
[0139] Comparative Example 2
[0140] The positive electrode material is prepared according to the method of Example 1, except that: Not carrying out step (1); and In step (2), 24.04 g of lithium carbonate (lithium source), 95.93 g of iron phosphate (iron source, phosphorus source), 44.08 g of manganese carbonate (manganese source), 0.05 g of calcium oxide (Ca), and 14.34 g of glucose (carbon source) were mixed with 200 g of pure water, and the mixture was ball-milled in a planetary ball mill at a rotation speed of 500 rpm for 6 h, and then the mixture was subjected to ball milling. 50 A slurry having a particle size of 0.62 μm is obtained, in which the molar ratio of the lithium source as Li, the phosphorus source as P, the carbon source as C, the iron source as Fe, the manganese source as Mn, and the calcium oxide as Ca is 1:1:0.1:0.4:0.6:0.0001, and the solid content of the slurry is 30 wt %. The other is not to add TiN nanoparticles in step (3).
[0141] After the olivine-type positive electrode material D2 was prepared, the composition, content of composite phases, particle size, pressed density and electrical resistivity of the olivine-type composite positive electrode material D2 were tested, and the results are shown in Table 1.
[0142] Comparative Example 3
[0143] The positive electrode material is prepared according to the method of Example 1.
[0144] Step (1) is the same as step (1) in the first embodiment.
[0145] In step (2), 24.28 g of lithium carbonate (lithium source), 99.96 g of iron nitrate (iron source), 132.83 g of manganese nitrate (manganese source), 73.52 g of phosphoric acid (phosphorus source), 0.33 g of barium nitrate (Ba), and 62.52 g of glucose (carbon source) are mixed with 200 g of pure water, and the mixture is stirred with a mechanical mixer at a rotation speed of 300 rpm for 6 h to obtain a slurry, in which the molar ratio of the lithium source (Li), the phosphorus source (P), the carbon source (C), the iron source (Fe), the manganese source (Mn), and the barium nitrate (Ba) is 1:1:0.1:0.4:0.6:0.0008, and the solid content of the slurry is 45 wt%.
[0146] Step (3) of Example 1 is not performed.
[0147] In step (4), the second heat treatment conditions are as follows: the slurry is treated at 750° C. for 8 h, a sinter is obtained, and the sinter is pulverized in an air jet mill to an average particle size D 50 is 1.5μm and the chemical formula is LiMn 0.6 Fe 0.398 Ba 0.002 PO4C 0.1 The crushed material is obtained.
[0148] In step (5), the LiMn 0.6 Fe 0.398Ba 0.002 PO4C 0.1 The crushed material and the TiN nanoparticles obtained in step (1) were mixed in a ball grinding can at a rotation speed of 850 rpm for 4 h to obtain a mixture, which was then heat-treated at 600 °C for 4 h under a nitrogen gas atmosphere to finally obtain the TiN nanoparticles with the chemical formula LiMn 0.6 Fe 0.398 Ba 0.002 PO4C 0.1 An olivine-type cathode material D3 of @TiN is obtained, where the dosage of TiN nanoparticles is 15 wt% for the crushed material of LiMn0.6Fe0.398Ba0.002PO4C0.1.
[0149] Some of the materials were taken and scanned by EDS surface to test the distribution uniformity of Ti element in the materials, and the results are shown in Table 1.
[0150] The composition, content of composite phase, particle size, pressed density, electrical resistivity and T / G of the olivine-type composite cathode material D3 were tested, and the results are also shown in Table 1.
[0151] [Table 1]
[0152] [Table 2]
[0153] As can be seen from Table 1, the positive electrode materials produced in Examples 1 to 6 have a high pressed density and a low electrical resistivity compared to Comparative Examples 1 to 3. Specifically, the pressed density is generally 2 g / cm 3 The electrical resistivities are all greater than 500 Ω·cm. At the same time, the distribution of the T element is uniform in the positive electrode materials produced in Examples 1 to 6, so that the electrical performance, particularly the high-power performance, of the lithium-ion batteries assembled from the above-mentioned positive electrode materials is excellent. On the other hand, the electrical resistivities of the positive electrode materials produced in Comparative Examples 1 to 3 are all greater than 2500 Ω·cm, and the distribution of the T element is non-uniform, so that the electrical performance of the lithium-ion batteries assembled from the positive electrode materials is poor, and the deterioration of the power performance is remarkable.
[0154] Figure 1 is a distribution diagram of T of the sintered material of Example 3, and Figure 2 is a distribution diagram of T of the sintered material of Comparative Example 3. As can be seen from Figures 1 and 2, the distribution of N element is relatively uniform in Figure 1, while the distribution of N element is non-uniform and there are many clumps in Figure 2. This indicates that the composite phase of the sample produced by the present invention is uniformly distributed within the substrate, and can better play the role of improving the electron transmission of the surface and improving the stability of the surface structure.
[0155] Test example 1
[0156] Regarding the manufacturing method of the liquid lithium-ion battery, the olivine type positive electrode material of the embodiment and the comparative example, acetylene black and polyvinylidene fluoride (PVDF) are mixed in a mass ratio of 90:5:5, applied to aluminum foil, and then dried. Next, the positive electrode sheet is punched out at a pressure of 100 MPa to a diameter of 12 mm and a thickness of 120 μm. The positive electrode sheet is then dried in a vacuum drying oven at 120 °C for 12 h. A Li metal sheet with a diameter of 17 mm and a thickness of 1 mm is used as the negative electrode. A Celgard 2400 porous membrane with a thickness of 25 μm is used as the separator, and an equal mixture of 1 mol / L LiPF6, ethylene carbonate (EC) and diethyl carbonate (DEC) is used as the electrolyte. The positive electrode sheet, separator, negative electrode sheet and electrolyte are assembled in an Ar gas glove box with moisture and oxygen contents all less than 5 ppm to create a 2025-type coin cell. The assembled coin cells were capacity tested at 0.1C and 2C scaling factors in a 25°C environment and cycled at 1C scaling factor for 100 cycles, and the results are shown in Table 2.
[0157] [Table 3]
[0158] 3 shows charge / discharge curves at 0.1C and 2C of the liquid lithium ion batteries assembled with the positive electrode materials of Comparative Example 3 and Example 1. FIG. 4 shows the cycling performance at 1C of the liquid lithium ion batteries assembled with the positive electrode materials of Comparative Example 3 and Example 1. As can be seen from Table 2, FIG. 3 and FIG. 4, the liquid lithium ion batteries assembled with the positive electrode materials prepared according to the embodiments of the present invention are significantly superior in discharge capacity, high-rate performance and cycling retention rate to the liquid lithium ion batteries assembled with the positive electrode materials prepared according to the comparative examples.
[0159] Test example 2
[0160] Regarding the manufacturing method of the all-solid-state lithium battery, the olivine type positive electrode material of the embodiment and the comparative example, conductive carbon black, and polyvinylidene fluoride (PVDF) are mixed in a mass ratio of 90:5:5, an appropriate amount of NMP is added and stirred uniformly, then the mixture is applied to aluminum foil by the doctor blade method, dried for 1 h in a forced air drying oven at 120 ° C, and punched into a positive electrode sheet with a diameter of 11 mm. Metallic lithium is used as the negative electrode, and a PEO-based solid electrolyte film is used as the electrolyte. In an Ar gas glove box with a moisture and oxygen content of less than 5 ppm, the manufactured positive electrode sheet, composite electrolyte film, and negative electrode are assembled to create a 2025-type coin cell. The assembled coin cell is tested for capacity at 2C magnification in an environment of 25 ° C and cycled for 100 cycles at 1C magnification, and the results are shown in Table 3.
[0161] [Table 4]
[0162] As can be seen from Table 3, the solid-state lithium ion battery assembled with the cathode material prepared according to the embodiment of the present invention is significantly superior in both high-power performance and cycle retention rate to the solid-state lithium ion battery assembled with the cathode material prepared according to the comparative example.
[0163] Test Example 3
[0164] Regarding the preparation method of the liquid lithium-ion battery, the positive electrode material, acetylene black and polyvinylidene fluoride (PVDF) are mixed in a mass ratio of 90:5:5, applied to aluminum foil, and then dried. Next, the positive electrode sheet with a diameter of 12 mm and a thickness of 120 μm is punched out at a pressure of 100 MPa. The positive electrode sheet is then dried in a vacuum drying oven at 120 °C for 12 h. A standard graphite negative electrode is used as the negative electrode, a 25 μm thick Celgard 2400 porous membrane is used as the separator, and an equal mixture of 1 mol / L LiPF6, ethylene carbonate (EC) and diethyl carbonate (DEC) is used as the electrolyte. The positive electrode sheet, separator, negative electrode sheet and electrolyte are assembled in an Ar gas glove box with moisture and oxygen contents all less than 5 ppm to create a 2025-type coin cell. The assembled coin cell was cycled at 1C for 1000 cycles in a 45°C environment, and the battery after cycling was dissected to obtain the negative electrode. The manganese content in the negative electrode was tested by ICP, and the results are shown in Table 4.
[0165] [Table 5]
[0166] As can be seen from Table 4, the liquid lithium ion batteries assembled with the positive electrode materials prepared according to the embodiments of the present invention have significantly lower manganese elution amounts after long-term cycling than the liquid lithium ion batteries assembled with the positive electrode materials prepared according to the comparative examples.
[0167] Although the preferred embodiment of the present invention has been described in detail above, the present invention is not limited thereto. Within the scope of the technical idea of the present invention, many simple modifications can be made to the technical content of the present invention, including combining each technical feature in any other suitable manner. These simple modifications and combinations are also considered as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. An olivine-type composite positive electrode material, the composite positive electrode material comprises a substrate and a composite phase; The substrate has a composition according to formula I: Li x M 1 y Mn z Fe 1-z-u M 2 u (PO 4 ) w (RO a ) b Cv (Formula I) Among them, 0.5≦x<1.3, 0≦y≦0.5, 0<z≦1, 0≦u≦0.01, 0<w≦1, 0<v≦0.05, 0≦a≦8, 0≦b≦1, M 1 is at least one element selected from Mg, Na, and K, M 2 is at least one element selected from Ga, Sn, V, Y, Mo, Al, Mg, Ce, Ti, Zr, Nb, Si, W, and In, and R is at least one element selected from Si, Cl, Br, S, Sb, and Sn, The composite phase has a composition shown in Formula II, T m G n (Formula II) wherein 0.1≦m≦5, 0.1≦n≦5, T is at least one element selected from Ti, Mo, Co, W, Zn, Cu, B, V, Nb, Ta, Pd, Cr, Ag, Al, Mn, Sn, Mg, Sc, Zr, and Hf, and G is an element selected from N and / or C.
2. In formula I, 0.9≦x<1.1, 0<y≦0.01, 0.5≦z≦1, 0<u≦0.005, 0.5≦w<1, 0.001<v≦0.03, 0≦a≦4, 0<b≦0.1, 2. The olivine type composite positive electrode material according to claim 1, wherein, in formula II, 0.5≦m≦3, 1≦n≦5, and T is at least one element selected from Ti, Mo, Co, W, Zn, Cu, B, V, Nb, Ta, Cr, Ag, Al, Mn, Sn, Mg, Sc, and Zr.
3. 3. The olivine-type composite cathode material according to claim 1 or 2, wherein the content of said composite phase is 0.01-10 wt %, preferably 0.01-1 wt %, based on the total weight of the composite cathode material.
4. The pressed density of the composite positive electrode material is 1.5 to 3 g / cm 3 and preferably 2 to 3 g / cm 3 and Preferably, the electrical resistivity of the composite cathode material is ≦2500 Ω / cm, preferably ≦1000 Ω / cm; Preferably, in the composite positive electrode material, 0.5≦m / n≦7, preferably 1≦m / n≦5; Preferably, the average particle size D of the composite positive electrode material 50 is 0.5 to 20 μm, preferably 1 to 15 μm, The olivine type composite cathode material according to any one of claims 1 to 3, wherein the composite cathode material has an EDS elemental analysis with a standard dispersion of m / n at any position of ≦1%.
5. A method for producing an olivine type composite positive electrode material, comprising the steps of: (1) performing a first mixing process on a compound containing a T element and a compound containing a G element to obtain a first mixture, and performing a first heat treatment on the first mixture in the presence of a protective atmosphere to obtain a compound containing T and G; A lithium source, a carbon source, a phosphorus source, an optional iron source, a manganese source, an optional R source, and an optional M source. 1 source and, optionally, M 2 (2) subjecting the source and the solvent to a second mixture to obtain a second mixture, and grinding the second mixture to obtain a slurry; (3) performing a third mixing and drying of the compound containing T and G and the slurry to obtain a powder; and (4) subjecting the powder to a second heat treatment in the presence of a non-oxidizing gas atmosphere to crush it to obtain the olivine-type composite positive electrode material.
6. In step (1), the compound containing the T element is at least one selected from the group consisting of an elemental T, an oxide of T, a nitrate of T, and a hydroxide of T; Preferably, the compound containing the G element is at least one selected from nitrogen gas, ammonia gas, melamine, polydopamine, urea, glucose, starch, sucrose, and graphite; Preferably, the conditions of the first heat treatment include a heat treatment temperature of 400 to 1000° C. and a heat treatment time of 2 to 8 h; The method according to claim 5, wherein the molar ratio of the T element in the compound containing the T element to the G element in the compound containing the G element is preferably 0.5 to 7:
1.
7. In step (2), the lithium source is at least one selected from lithium carbonate, lithium hydroxide, lithium oxide, and lithium nitrate; Preferably, the phosphorus source is at least one selected from phosphoric acid, metaphosphoric acid, pyrophosphoric acid, ammonium dihydrogen phosphate, diamine hydrogen phosphate, and phosphorus oxide; Preferably, the carbon source is at least one selected from glucose, sucrose, starch, graphene, and carbon nanotubes; Preferably, the iron source is at least one selected from iron phosphate, iron oxalate, iron acetate, iron oxide, and iron oxyhydroxide; Preferably, the manganese source is at least one selected from manganese oxide, manganese carbonate, and manganese nitrate; Preferably, the R source is selected from compounds containing at least one element of Si, Cl, Br, S, Sb and Sn; Preferably, the M 1 the source is selected from compounds containing at least one of the elements Mg, Na and K; Preferably, the M 2 the source is selected from compounds containing at least one element of Ga, Sn, V, Y, Mo, Al, Mg, Ce, Ti, Zr, Nb, Si, W and In; Preferably, the solvent is at least one selected from water, ethanol, methanol, NMP, and isopropanol; Preferably, the moles of the lithium source as Li, the moles of the phosphorus source as P, the moles of the carbon source as C, the moles of the iron source as Fe, the moles of the manganese source as Mn, the moles of the R source as R, the moles of the M 1 Source M 1 and the molar ratio of M 2 Source M 2 and the molar ratio of the molar amounts of the compounds as the above is (0.5-1.3):(0-1):(0-0.05):(0-1):(0-1):(0-1):(0-1):(0-0.5):(0-0.01), Preferably, the solids content of the slurry is 10-60 wt %; Preferably, the average particle size of the slurry is D 50 The method according to claim 5 or 6, wherein the thickness is 0.1 to 1 μm.
8. In step (3), the solid-liquid ratio of the compound containing T and G to the slurry is 0.000001 to 10 g / mL; Preferably, in step (4), the conditions of the second heat treatment include a heat treatment temperature of 400 to 1000° C. and a heat treatment time of 4 to 12 hours.
9. An olivine type composite positive electrode material produced by the method according to any one of claims 5 to 8.
10. The application of the olivine-type composite positive electrode material according to any one of claims 1 to 4 and 9 in at least one of a supercapacitor, a lithium-ion battery, and a lithium-sulfur battery.
11. A lithium ion battery comprising the olivine type composite positive electrode material according to any one of claims 1 to 4 and 9.
12. The lithium ion battery according to claim 11, wherein the lithium ion battery is a liquid lithium ion battery, and after cycling at 45°C for 1000 cycles, the amount of manganese leaching from the negative electrode of the liquid lithium ion battery is ≦3000 ppm, preferably 500-2000 ppm.
Citation Information
Patent Citations
Lithium manganese phosphate composite cathode material and preparation method and application thereof
CN106450304A
Electrode material and method for producing the same, electrode and lithium ion battery
JP2013069566A